A single dose of the novel chimeric subunit vaccine E2-CD154 confers early full protection against classical swine fever virus. Issue 34 (3rd August 2017) - Suárez, Marisela; Sordo, Yusmel; Prieto, Yanet; Rodríguez, María P.; Méndez, Lídice; Rodríguez, Elsa M.; Rodríguez-Mallon, Alina; Lorenzo, Elianet; Santana, Elaine; González, Nemecio; Naranjo, Paula; Frías, María Teresa; et al.
Highlights: A stable HEK 293 cell line was generated to produce E2-CSFV antigen fused to CD154. The E2-CD154 protein was secreted into the medium in suspension culture. The E2-CD154 obtained was glycosylated and mainly forming protein aggregates. First report of a subunit vaccine conferring protection 7 days after single dose. Specific anti-CSFV neutralizing antibodies and IFN-γ were induced 8 dpc (14 dpv). Abstract: Classical swine fever is an economically important, highly contagious disease of swine worldwide. Subunit vaccines are a suitable alternative for the control of classical swine fever. However, such vaccines have as the main drawback the relatively long period of time required to induce a protective response, which hampers their use under outbreak conditions. In this work, a lentivirus-based gene delivery system is used to obtain a stable recombinant HEK 293 cell line for the expression of E2-CSFV antigen fused to porcine CD154 as immunostimulant molecule. The E2-CD154 chimeric protein was secreted into the medium by HEK293 cells in a concentration around 50 mg/L in suspension culture conditions using spinner bottles. The E2-CD154 immunized animals were able to overcome the challenge with a high virulent CSF virus strain performed 7 days after a unique dose of the vaccine without clinical manifestations of the disease. Specific anti-CSFV neutralizing antibodies and IFN-γ were induced 8 days after challenge equivalent to 14 days post-vaccination. The present work constitutes the first report of a subunit vaccine able to confer complete protection by the end of the first week after a single vaccination. These results suggest that the E2-CD154 antigen could be potentially used under outbreak conditions to stop CSFV spread and for eradication programs in CSF enzootic areas.